The Fluidity Characteristics of Liquid Duralumin by Piece Test Methode on Permanent Mold in Low Pressure - Suprapto, Wahyono (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
The shrinkage and porosity is the casting failures which is often found in the casting products especially aluminum alloys. That failure is happen because the liquid metals cooling processes is not uniform or there is pit-fall gasses. The shrinkage and porosity significationcould reduce material mechanics characteristic significantly. The controlling parameters of the vibration the metals solidifications is implicated to the improvement of aluminum alloys casting products qualities.The objective of this experiment research is to compare the properties on castability, formability, and sub-surface defect on a piece duralumin cast of permanent mold casting. Low pressure mold cavity is an independent variable and fluidity, ductility, porosity are dependent variables, and pouring temperature is a control parameter which is plant in this research design. The research conclusion is while the pressure decrease on cavity would increase castability, ductility, and could reduced the sub-surface defect on duralumin casting.Keywords: fluidity, liquid duralumin, low pressure, solidification, sub-surface defect